Great apes and humans evolved from a long-backed ancestor. Issue 144 (July 2020) - Machnicki, Allison L.; Reno, Philip L.
Abstract: There is current debate whether the Homo / Pan last common ancestor (LCA) had a short, stiff lumbar column like great apes or a longer, flexible column observed in generalized Miocene hominoids. Beyond having only four segments, three additional features contribute to lumbar stiffening: the position of the transitional vertebra (TV), orientation of the lumbar spinous processes, and entrapment of lumbar vertebrae between the iliac blades. For great apes, these features would be homologous if inherited from a short-backed LCA but likely functionally convergent through dissimilar phenotypes if evolved from a long-backed LCA. We quantitatively and qualitatively analyzed human, ape, and monkey thoracic and lumbar vertebrae using 3D surface scanning and osteological measurements to compare spinous process morphology and sacral depth. We also used a large sample of hominoid vertebral counts to assess variation in the position of the TV and lumbosacral boundary. All extant hominoids modally place the TV at the ultimate thoracic. However, humans and orangutans place the TV at the 19th postcranial vertebral segment, whereas other apes place the TV at the 20th. Furthermore, chimpanzees, gorillas, and orangutans each have distinct patterns of spinous process angulation and morphology associated with lumbar stiffening, while human spinous process morphology is similar to that of longer backed gibbons, monkeys, and Miocene hominoids Morotopithecus and Pierolapithecus . Finally, chimpanzees are unique compared with other hominoids with a greater sacral depth facilitating lumbar entrapment, and there are differences among African apes with respect to the mechanisms governing variation in the lumbosacral boundary. These differences suggest that lumbar stiffening is convergent among great apes and that human bipedalism evolved from a more generalized long-backed ancestor. Such a model is more consistent with evidence of TV placement in Australopithecus .